Electropolymerized poly(3-aminobenzoic acid)-based surface plasmon resonance immunosensor - Saengrawee Sriwichai (2018)
The surface plasmon resonance immunosensor based on carboxylated polyaniline was constructed in this study. The carboxylated polyaniline, poly(3-aminobenzoic acid) (PABA), was prepared by electropolymerization of its monomer, aminobenzoic acid (ABA), on a gold electrode. The kinetic property during the electropolymerization was in-situ monitored with electrochemical surface plasmon resonance spectroscopy. The obtained polymer film showed an electroactivity in PBS buffer solution. The obtained electrode can be used for human antibody immobilization to study the binding reaction between the antibody and antigen. The immobilization and binding reaction processes were also in situ studied by surface plasmon resonance spectroscopy.